Inaccuracies in calculating predicted body weight and its impact on safe ventilator settings. (August 2016) - O'Brien, Ian David; Shacklock, Emma; Middleditch, Alex; Bigham, Colin
In many centres, height is used as a determinant for calculating predicted body weight. This predicted body weight is then multiplied to generate the desired tidal volume. The approach exhibits some mathematical effects: (1) any errors in height measurement are multiplied by 5.5 when generating the tidal volume (assuming 6 ml/kg); (2) any errors in height measurement have a greater impact on shorter patients. The aim of this study was to: (1) establish the current practice of setting a tidal volume in England; (2) assess the implications of inaccurate height measurements on tidal volume settings using the most common practice; (3) identify the most accurate and precise method of determining height to aid accurate application of a lung protective strategy. The six extra corporeal membrane oxygenation centres in the UK, and the 34 intensive cares with the highest admission figures were identified from the intensive care national audit and research centre database. Most frequent practice was to use of a 1-m tape on the supine patient on admission. Inaccuracies in height estimation using a 1-m tape resulted in a standard deviation of 23 ml and a spread of over 120 ml tidal volume in individual patients.There are a number of methods of estimating height in a supine patient but the most accurate appeared to be simply using a 2-m tape.